2009
DOI: 10.1007/s10071-009-0215-2
|View full text |Cite
|
Sign up to set email alerts
|

Its own reward: lessons to be drawn from the reversed-reward contingency paradigm

Abstract: This is a review of the reversed-reward contingency (RRC) paradigm in animals and the cognitive functions on which it is founded. I shall present the RRC basic paradigm and the ensuing modifications it underwent, the animals tested, the results obtained and the analyses offered within the literature. Then I would the claim that RRC is a case of a compound cognitive behavior, one that is the result of interactions between three other cognitive functions: crude numerical assessment and economic choice (uniting v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 66 publications
1
40
1
2
Order By: Relevance
“…It is possible that this bias stemmed from a more general problem of inhibiting responses to visibly present food items. Such inhibitory issues have been documented in animals in other cognitive paradigms, most notably the reversed-reward contingency task devised by Boysen and her colleagues (e.g., Boysen & Bernston, 1995; for a review of research conducted with this paradigm see Shifferman, 2009). However, these monkeys did not exhibit this bias in previous experiments in which they compared entirely visible food sets to food sets presented item-by-item into an opaque container (Evans et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that this bias stemmed from a more general problem of inhibiting responses to visibly present food items. Such inhibitory issues have been documented in animals in other cognitive paradigms, most notably the reversed-reward contingency task devised by Boysen and her colleagues (e.g., Boysen & Bernston, 1995; for a review of research conducted with this paradigm see Shifferman, 2009). However, these monkeys did not exhibit this bias in previous experiments in which they compared entirely visible food sets to food sets presented item-by-item into an opaque container (Evans et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Past research had indicated that chimpanzees and other species typically failed to learn to point to less valuable rewards to gain more valuable ones in the reverse-reward task (at least without extensive experience or arbitrary token substitutions; see Shifferman, 2009). The three chimpanzees in this study showed the same failure.…”
Section: Discussionmentioning
confidence: 99%
“…While this premise appears reasonable, a direct correlation between reversal learning and inhibitory control still needs to be shown. However, if the better than expected performance of marmosets in reversal learning is due to better inhibitory control, they should also perform better than expected for their size in inhibitory control tasks, such as detour reaching [MacLean et al, 2012], delay tolerance [Addessi et al; Amici et al, 2008] or reversed reward contingency [Shifferman, 2009].…”
Section: Discussionmentioning
confidence: 99%